André Maurois (1885-1967) Fortunes and Misfortunes of a Moderate - Gossman, J.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Pivot, 2014)
Respected by his peers and hugely successful internationally in his own time, André Maurois is now hardly read. Moderate and conciliatory in everything, including his literary style, he appealed to the educated reader of his time, but did those very qualities prevent him from achieving lasting distinction and impact?
Keywords: European literature; Literature—History and criticism; World War, 1939-1945.; Literature, Modern—20th century; Fiction; Europe—History.; European Literature; Literary History; History of World War II and the Holocaust; Twentieth-Century Literature; Fiction; European History